General Director of LLC «Center of Pharmaceutical Analytics» Igor Shohin received the PEOPLE OF THE YEAR 2024 award at the Chamber of Commerce and Industry of the Russian Federation - article Editorial (Разработка и регистрация лекарственных средств, 2024)
On May 31, 2024, for the sixth time, the "Russian Business Guide. PEOPLE OF THE YEAR" award was held at the Congress Center of the Russian Chamber of Commerce and Industry. The gala event is held with the support of the Chamber of Commerce and Industry of the Russian Federation.